Purpose in Life in Higher Education: Is There a Role for Service-Learning? - Luísa Mota Ribeiro; Alexandra Doroftei; Francisca Miranda; Carmo Themudo; Paulo Dias; Ricardo Peixoto; Ana Oliveira; Maria Correia; Pilar Aramburuzabala; Pedro Rosário; Robert G. Bringle (MDPI AG, 2023)
The current study analyzed university students' purpose in life in the context of service-learning (SL) courses developed in a university in Portugal. Briefly, 112 graduation and master students, from different areas, involved in 15 SL courses (82 female; 73.2%; age ranging from 18 to 51; M = 23; SD = 6.51) participated in this study. Questionnaires included an open-ended question about students' purpose in life. Four closed-ended questions were included to understand student's perceptions of change in their purpose in life arising from the SL courses and other perceptions about their SL course. Qualitative data were analyzed via content analysis with NVivo. Results indicated that students' purpose in life ranged from social-related goals, such as helping or caring for others, to personal-related goals, including personal growth and well-being. Most of the students (71.4%) reported that their purpose in life changed moderately or a lot after participating in a SL course. Findings are discussed in light of the literature, identifying implications for the development of SL courses in higher education, considering the contribution of this pedagogic methodology to the definition and reconfiguration of young people's purpose in life.